Optimalisasi Pembelajaran Pada Mata Pelajaran Ilmu Pengetahuan Sosial (Ips) Melalui Pengorganisasian Tugas Terstruktur Dan Kuis Untuk Meningkatkan Kemandirian Belajar Pada Siswa KELAS VIIB SMP N 03 Polokarto Tahun Ajaran 2015/2016 - WINASTUTI SUBANDI, RETNANING; , Dr.Suyatmini,SE.,M.Si (2016)
The purpose of this study to determine: 1) The process of learning in social studies through structured tasks and quizzes, 2) Increased independence of students in learning social studies in grade students VIIB SMP N 03 Polokarto through structured tasks and quizzes. This research is a classroom action research conducted in three cycles. Subjects receiver is class action VIIB SMP N 03 Polokarto totaling 32 students and the subject of implementation of the action is a social studies teacher and researcher. Data collection methods used are observation, field notes, documentation, and test methods. Data analysis technique used is descriptive qualitative with interactive analysis consists of data reduction, data presentation and conclusion. The results showed an increase in students' independent learning through organizing structured assignments and quizzes. It can be seen from: 1) confident, bold expression of students without a teacher appointed by the increase of the prior actions have 6 students (18.75%), the first cycle there are 10 students (31.25%), the second cycle there are 15 students (46.87%), the third cycle there were 24 students (75%), 2) the responsibilities, the students responsible for chores and quizzes given by teachers increased from before action there are 8 students (25%), the first cycle there are 15 students (46.87%), the second cycle there are 21 students (65.62%), the third cycle there are 26 students (81.25%), 3) initiative, the student initiative to ask about the material that does not understand there is increasing from prior measures 4 students (12.5%), the first cycle there are 9 students (28.12%), the second cycle there were 17 students (53.12%), the third cycle there were 23 students (71.87%), 3) discipline, students gather assignments on time increased from before action there were 15 students (46.87%), the first cycle there are 20 students (62.5%), the second cycle there were 24 students (75%), the third cycle there were 28 students (87.5%) , This study suggests that the application of a structured method of organizing tasks and quizzes can improve student learning independence.